Self-Reported Non-Celiac Gluten Sensitivity in Brazil: Translation, Cultural Adaptation, and Validation of Italian Questionnaire - Gadelha de Mattos, Yanna A. (Nutrients, 2019)
This study aimed to translate, culturally adapt, validate, and apply a questionnaire to the Brazilian non-celiac gluten sensitive (NCGS) population. We also aimed to estimate the prevalence of symptoms which affect Brazilian NCGS. The Brazilian Portuguese version of the NCGS questionnaire was developed according to revised international guidelines. Five-hundred-and-fourty-three participants responded the NCGS questionnaire. We evaluated the reproducibility and validity of the questionnaire which presents valid measures of reproducibility. This is the first specific self-reported validated questionnaire for NCGS patients in Brazilian Portuguese, and the first nationwide characterization of self-reported NCGS in Brazilian adults. Most respondents were female (92.3%), and the main intestinal symptoms reported were bloating and abdominal pain. The most frequent extraintestinal symptoms were lack of wellbeing, tiredness, and depression. We expect that the present study will provide a picture of Brazilian individuals with suspected NCGS, which could help health professionals and governmental institutions in developing effective strategies to improve the treatment and diagnosis of Brazilian NCGS.